DEVELOPMENT OF CARDIOMYOPATHY IN DIABETES MELLITUS - Ergashov Bekhruzjon Komilovich (PEDAGOGS, 2024)
Annotation: clinical manifestations of types of cardiomyopathy in combination with diabetes mellitus, symptoms both diseases, the clinical symptoms of which disease are more pronounced, general andvarious symptoms in the clinical course.